PERLINDUNGAN KONSUMEN DALAM PERSPEKTIF SYARIAH: Kajian Pustaka Prinsip ‘Adl, Sidq dan Larangan Gharar serta Riba - Rozan Avif, Rozan Avif; Muhammad Julijanto, Muhammad Julijanto (JSE: Jurnal Sharia Economica, 2026)
Consumer protection is a central issue in modern law, particularly in the context of increasingly complex global trade, which often creates information asymmetry between businesses and consumers. Law No. 8 of 1999 on Consumer Protection provides a formal legal framework, yet it has not fully accommodated the moral and spiritual dimensions that play a crucial role in ensuring transactional justice. From the perspective of Islamic law, the principles of ‘adl (justice) and ṣidq (honesty) serve not only as ethical foundations but also as obligatory elements of every contract, while the prohibitions of gharar (uncertainty) and ribā (financial exploitation) function as preventive mechanisms against practices harmful to consumers. This study employs a normative juridical method with a library research approach to analyze the relationship between sharia principles and consumer protection law in Indonesia. The findings reveal that consumer protection from a sharia perspective is more comprehensive than positive law alone, as it integrates substantive justice, morality, and spirituality. Thus, sharia principles can enrich the national legal system and strengthen the effectiveness of consumer protection in Indonesia.